2007
DOI: 10.1021/ar700113g
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Asymmetric Hydrogenation of Olefins

Abstract: Asymmetric hydrogenation is one of the most important catalytic methods for the preparation of optically active compounds. For a long time the range of olefins that could be hydrogenated with high enantiomeric excess was limited to substrates bearing a coordinating group next to the C+C bond. We have found a new class of catalysts, iridium complexes with chiral P, N ligands, that overcome these limitations. For a wide range of unfunctionalized olefins, excellent enantioselectivities could be achieved. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
185
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 586 publications
(193 citation statements)
references
References 70 publications
3
185
1
4
Order By: Relevance
“…These successful results have significantly adv a n c e d t h i s a r e a o f r e s e a r c h w i t h t h e development of numerous chiral P,N-ligands [13,[54][55][56][57][58]. Representatives of the chiral iridium complexes so far reported are shown in Fig.…”
Section: Scheme 19 Anion Effect On the Hydrogenation Of (E)--methylmentioning
confidence: 94%
“…These successful results have significantly adv a n c e d t h i s a r e a o f r e s e a r c h w i t h t h e development of numerous chiral P,N-ligands [13,[54][55][56][57][58]. Representatives of the chiral iridium complexes so far reported are shown in Fig.…”
Section: Scheme 19 Anion Effect On the Hydrogenation Of (E)--methylmentioning
confidence: 94%
“…The corresponding air-stable [(PN) Ir(cod)].BAr F complexes were obtained in good yields (60-88%) following literature procedures (Scheme 2). [11] Preliminary investigations on a model substrate showed that (i) these complexes displayed a catalytic activity similar to the achiral catalyst 1, (ii) the reaction was highly dependent on the size of the P-alkyl substituents; the bulkier substituents leading to the highest enantioselectivities. Under the optimized conditions, the isomerization product was obtained with unprecedented yield and enantioselectivity (98% yield, 95% ee or 75% yield, 97% ee).…”
Section: Isomerization Of Primary Allylic Alcoholsmentioning
confidence: 99%
“…4 More recently, homogeneous iridium catalysed asymmetric hydrogenation allows, through excellent enantio-selectivity and atom economy, the efficient synthesis of chiral compounds, especially building blocks. 5 After Pfaltz' improvement on Crabtree's catalyst, methods of iridium catalyzed asymmetric hydrogenation were developed extensively. 6 These new catalysts were obtained by replacing the previously used PF 6…”
Section: Introductionmentioning
confidence: 99%